A facile approach for the fabrication of antibacterial nanocomposites: A case study for AgNWs/Poly(1, 4-Cyclohexanedimethylene Acetylene Dicarboxylate) composite networks by aza-Michael addition. (15th April 2022) - Altinkok, Cagatay; Acik, Gokhan; Daglar, Ozgun; Durmaz, Hakan; Tunc, Ilknur; Agel, Esra
Graphical abstract: Highlights: The facile and versatile strategy for nanocomposite fabrication is firstly proposed. Effect of AgNWs loading on different properties of resulting nanocomposite networks is investigated. AgNWs and Poly(1, 4-Cyclohexanedimethylene Acetylene Dicarboxylate) based nanocomposite networks possess the good thermal and antibacterial features. More effort is necessary to manufacture new commercial products based on this strategy. Abstract: Nanotechnological improvements allow the production of new generation materials among which nanocomposite-based polymers are increasingly applied for wide variety of applications due to the demand increment of improving life quality of mankind. This article describes a simple, facile and fast route which could be adopted for the synthesis of metal nanocomposite materials with a variety of polymers. In this purpose, the cysteamine compound containing an amine (–NH2 ) and a thiol (–SH) functional groups was incorporated onto silver nanowires (NH2 -AgNWs). Next, poly(1, 4-Cyclohexanedimethylene Acetylene Dicarboxylate) (PCA) possessing electron deficient internal alkyne moiety is synthesized starting from acetylene dicarboxylic acid (ADCA). Finally, one-pot aza-Michael addition is then realized between prepared NH2 -AgNWs and synthesized PCA to achieve a series of cross-linked antibacterial nanocomposite networks (PCA:NH2 -AgNWs = 1; 5; 10 wt%). The nanocomposites and intermediates are fully characterized by Fourier transform infrared and proton nuclear magnetic resonance (FT-IR, 1 H NMR) spectroscopies, gel permeation chromatography (GPC) scanning electron microscopy (SEM), Energy–dispersive X-ray spectroscopy (EDS), thermogravimetric and differential scanning calorimetry analyses (TGA and DSC) and antibacterial test. The results reveal that the higher content of AgNWs in the network has occasioned the enhancement in thermostability and glass transition temperature. The antibacterial efficacy tests against Escherichia coli ( E. coli, G − ) and Staphylococcus aureus (S.aureus, G + ) further indicate that higher rate of inhibition is attained for nanocomposite network including 10 wt% AgNWs compared to others and pristine PCA. Consequently, a polyester based AgNWs/PCA nanocomposite with antibacterial activity has been considered as a versatile candidate for various promising nanocomposite applications.